2014
DOI: 10.1007/s12560-014-9172-2
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus and Rotavirus Survival in Urine Collected from a Public Ecological Sanitation System in Ouagadougou, Burkina Faso

Abstract: Urine from urine-diversion toilets (UDTs) is routinely used as fertilizer for urban agriculture in Ouagadougou, Burkina Faso. Because urine from UDTs can be accidentally spoiled by feces, we determined whether virulent enteric viruses could persist in urine that is used for agricultural purposes and pose a threat to human health. Urine samples (N = 60) were first collected from 42 UDTs during the months of January and February 2012 in Ouagadougou and screened negative for the presence of norovirus (NoV) and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The kinetic trends observed in this study were generally consistent with studies using real matrices (19,26,30,(34)(35)(36)58), although some works reported contradictory results (25,27,32,37). This may be due to the high complexity of real matrices compared to the well-controlled solutions used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The kinetic trends observed in this study were generally consistent with studies using real matrices (19,26,30,(34)(35)(36)58), although some works reported contradictory results (25,27,32,37). This may be due to the high complexity of real matrices compared to the well-controlled solutions used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…notably, previous research has proven inconclusive on the role of urine as a transmission pathway for faecal pathogens. A study by Bischel and colleagues (2015) found 100 per cent of urine samples collected from urine diversion sanitation systems had diarrhoeal bacteria representing a wide spectrum of faecal pathogens (Bischel et al, 2015), whereas a study by Makaya and colleagues (2015) found 100 per cent of urine samples negative for rotavirus (roV) and norovirus (noV) in a similar study (Makaya et al, 2015). The likelihood of faeces-to-urine cross-contamination, as well as the role of causal mechanisms and controls, are therefore areas of research that demand further exploration.…”
Section: Discussion: Combining Findings Of Environmental Contaminatiomentioning
confidence: 99%